Integrating information and communication technologies into the teaching and learning of science in Lesotho - Taolane, Bonnqe ‘Mamolibeli (University of the Free State, 2023)
Inligting- en kommunikasietegnologie (IKT)-integrasie in basiese onderwys word in sommige lande as ’n stryd beskou, al word die waarde van tegnologie in onderwys wêreldwyd waardeer. Wetenskaplikes het die onderbenutting van IKT erken en baie skole in ontwikkelende lande het óf geen IKT-infrastruktuur nie óf toestande stem nie ooreen met dié waar opleiding oor IKT-integrasie gehou is nie, Lesotho ingesluit. Hierdie kwalitatiewe, meervoudige gevallestudie het ondersoek hoe onderwysers IKT in Wetenskap gebruik, wat tans na verwys word as Wetenskap en Tegnologie by Basiese Onderwys in Lesotho, vanuit die interpretatiewe perspektief. Drie doelbewus geselekteerde graad 6 – 7 onderwysers is bestudeer deur die Tegnologiese Pedagogiese Inhoud Kennis-teorie (TPACK), ondersteun deur die High Possibility Classroom (HPC) model, met hul skoolhoofde betrokke by uittree-onderhoude. Die studie onthul die diskoerse wat onderwysers se IKT-integrasiepraktyke in Lesotho toelig en dokumenteer klaskamerpraktyke van IKT-integrasie in die onderrig van Wetenskap en Tegnologie in die hersiene kurrikulum. Laastens verduidelik dit die manier waarop onderwysers IKT integreer in die onderrig van Wetenskap in Lesotho. Bevindinge van inhoudsontleding van onderhoude, klaskamerwaarnemings en beleidsraamwerk het ’n paar interessante faktore aan die lig gebring wat bydra tot die manier waarop onderwysers IKT in Lesotho integreer. Die studie beklemtoon spesifiek die status van onderwysers se blootstelling aan produktiewe diskoerse wat IKT-integrasie motiveer. Dit openbaar verder die geselekteerde onderwysers se patrone van klaskamerpraktyke van IKT-integrasie, wat assessering van leerders se 21ste-eeuse vaardighede insluit en hoe kontekstuele beperkings tot IKT-integrasie gekonfronteer is. Die studie beklemtoon wenke van IKT-integrasie in die Beleidsraamwerke en leemtes in die Kurrikulum-en-Assesseringsbeleid, 2009, en die Wetenskap-en-Tegnologiekurrikulum vir graad 7. Die studie beveel deurlopende professionele ontwikkeling aan vir onderwysers om hul IKT-bevoegdhede en -pedagogie te versterk; onderwysers wat verantwoordelikheid neem om hul loopbane te verbeter om by die globale wêreld in te pas; ondersteuning vir ervare IKT-integrerende onderwysers om modelonderwysers vir IKT-pedagogie te word; en die ontwikkeling van praktykgemeenskappe oor IKT-integrasie. Die studie het die model vir effektiewe IKT-integrasie in laerskole voorgestel wat die onderwysstelsel, kurrikulum-ontwikkelaars, onderwysers en beleidmakers veral kan inlig oor IKT-beleid vir onderwys in Lesotho, wat tans in die konsepstadium is. Die studie dui verder die rigting aan vir toekomstige studies.

Information and communication technology (ICT) integration in Basic education has been regarded a struggle in some countries, even though the value of technology in education is globally appreciated. Scholars recognised the underutilisation of ICT and many schools in developing countries either have no ICT infrastructure or conditions do not match those where training on ICT integration was held, Lesotho included. This qualitative multiple case study investigated how teachers use ICT in science, currently referred to as Science and Technology at Basic Education in Lesotho, from the interpretive perspective. Three purposively selected Grade 6 - 7 teachers were studied through the Technological Pedagogical Content Knowledge (TPACK) theory, supported with the High Possibility Classroom (HPC) model with their principals engaged in exit interviews. The study reveals the discourses that inform teachers’ ICT integration practices in Lesotho and document classroom practices of ICT integration into the teaching of science and technology in the reviewed curriculum. Lastly, it accounts for the way teachers integrate ICT into teaching of science in Lesotho. Findings from content analysis of interviews, classroom observations and policy framework revealed some interesting factors that contribute to the way teachers integrate ICT in Lesotho. Specifically, the study highlights the status of teachers’ exposure to productive discourses motivating ICT integration. It further reveals the selected teachers’ patterns of classroom practices of ICT integration, incorporating assessment of learners’ 21st-century skills and how contextual constraints to ICT integration were confronted. The study highlights pointers of ICT integration in the Policy frameworks and gaps in Curriculum and Assessment Policy, 2009 and the Science and Technology curriculum for Grade 7. The study recommends Continuous Professional Development for teachers to strengthen their ICT competences and pedagogy; teachers taking responsibility for improving their careers to fit into the global world; support for experienced ICT-integrating teachers to become model teachers for ICT pedagogy and developing Communities of Practice on ICT integration. The study proposed the model for effective ICT integration in primary schools that could inform the education system, curriculum developers, teachers and policy makers especially, of ICT policy for education in Lesotho currently at draft stage. The study further suggests direction for future studies.

Ukuhlanganiswa kobuchwepheshe bolwazikuxhumana (ICT) kweMfundo Eyisisekelo kuthathwa njengomzabalazo kwamanye amazwe, nakuba ukubaluleka kobuchwepheshe kwezemfundo kwaziswa emhlabeni wonke. Izazi zibone ukusetshenziswa kancane kwe-ICT futhi izikole eziningi emazweni asathuthuka azinayo ingqalasizinda ye-ICT noma izimo azifani nalezo lapho ukuqeqeshwa kokuhlanganiswa kwe-ICT kwenziwa khona, kuhlanganisa neLesotho. Lolu cwaningo lwekhwalithethivu lwezimo eziningi luphenya ukuthi othisha bayisebenzisa kanjani i-ICT esayensini, okwamanje ebizwa ngokuthi iSayensi nobuChwepheshe eMfundweni Eyisisekelo eLesotho, ngokombono oqondayo. Othisha abathathu abakhethwe ngenhloso beBanga lesi-6 - 7 bacwaningwa ngenjululwazi iTechnological Pedagogical Content Knowledge (TPACK), imanyaniswa nemodeli iHigh Possibility Classroom (HPC) nothishanhloko babo behlanganyela ezingxoxweni zasebeshiya. Lolu cwaningo luveza izinkulumo ezazisa izindlela zothisha zokuhlanganisa i-ICT eLesotho futhi lubhala ngezinqubo zasekilasini zokuhlanganiswa kwe-ICT ekufundiseni isayensi nobuchwepheshe kwikharikhulamu ebuyekeziwe. Okokugcina, ilandisa ngendlela othisha abahlanganisa ngayo i-ICT ekufundiseni isayensi eLesotho. Okutholwe ekuhlaziyweni kokuqukethwe kwezingxoxo, okuqashelwe ekilasini kanye nohlaka lwenqubomgomo kwembula izinto ezithokozisayo ezinomthelela endleleni othisha abahlanganisa ngayo i-ICT eLesotho. Ngokucacile, ucwaningo lugqamisa isimo sokuchayeka kothisha ezinkulumweni ezisizayo ezikhuthaza ukuhlanganiswa kwe-ICT. Luphinde lwembule amaphethini othisha akhethiwe ezinqubo zasekilasini zokuhlanganiswa kwe-ICT, okuhlanganisa nokuhlolwa kwamakhono abafundi bekhulunyaka lama-21 kanye nokuthi kwabhekwana kanjani nezingqinamba zengqikithi ekuhlanganisweni kwe-ICT. Ucwaningo lugqamisa izinkomba zokudidiyelwa kwe-ICT ohlakeni Lwenqubomgomo kanye nezikhala eNqubomgomweni Yekharikhulamu Nokuhlola, yezi-2009 kanye nekharikhulamu yeSayensi Nobuchwepheshe yeBanga lesi-7. Lolu cwaningo luncoma Ukuthuthukiswa Kobungcweti Okuqhubekayo kothisha ukuze baqinise amakhono abo e-ICT nokufundisa; othisha abathatha isibopho sokuthuthukisa imisebenzi yabo ukuze babesezingeni elikahle lokusebenza emhlabeni jikelele; ukwesekwa kothisha abanolwazi lokuhlanganisa i-ICT ukuze babe yisibonelo sezindlela zokufundisa i-ICT kanye nokuthuthukisa Imigwamanda Yokufunda ukuhlanganiswa kwe-ICT. Lolu cwaningo luphakamise imodeli yokuhlanganiswa kwe-ICT okuphumelelayo ezikoleni zamabanga aphansi ezingazisa uhlelo lwezemfundo, abathuthukisi bekharikhulamu, othisha nabakhi benqubomgomo ikakhulukazi, benqubomgomo ye-ICT yezemfundo eLesotho esalungiswa njengamanje. Ucwaningo luphinde luphakamise izincomo zocwaningo lwesikhathi esizayo.

Kenyeletso ya theknoloji ya lesedi le dipuisano (ICT) thutong ya motheo e nkwa e le bothata dinaheng tse ding, le hoja bohlokwa ba theknoloji thutong bo ananelwa lefatsheng ka bophara. Barutehi ba etse hloko ho se sebediswe ka ho lekana ha ICT ebile dikolo tse ngata dinaheng tse holang ha di na ditshebeletso tsa ICT kapa ona maemo ha a tsamaelane le a moo thupello ya ho sebedisa ICT e neng e tshwaretswe teng, ho kenyelletswa le Lesotho. Diphuputso tsena tsa teko ya boleng bo menahaneng e ile ya fuputsa kamoo matitjhere a sebedisang theknoloji ya lesedi le dipuisano thutong ya saense, eo hona jwale e bitswang Saense le Theknoloji Thutong ya Motheo Lesotho, ho latela tekolo ya ditlhaloso. Matitjhere a mararo a kgethilweng ka boomo a Kereiti ya 6 - 7 a ile a lekolwa ka Technological Pedagogical Content Knowledge (TPACK), e tshehetswang ke mokgwa wa High Possibility Classroom (HPC) mme mesuwehlooho ya ona e bileng le teng dipuisanong tsa ona ho beha meja fatshe. Diphuputso di senola dipuo tse tataisang mekgwa ya matitjhere ya tshebetso e kenyelletsa ICT Lesotho le ho tsebisa ka mekgwa ya ho kenyelletsa ICT ka phaposing ya borutelo bakeng sa ho ruta saense le theknoloji lenaneong la thuto le lekotsweng botjha. Qetellong, e hlalosa tsela eo matitjhere a kenyelletsang ICT ka teng thutong ya saense Lesotho. Diphihlello tsa tlhahlobo ya dikateng tsa dipuisano, ho lebela ka diphaposing tsa borutelo le moralo wa leano, di senotse dintlha tse ding tse kgahlang tse tlatsetsang tseleng eo matitjhere a kenyang ICT ka yona Lesotho. Ka ho kgetheha, thuto ena e totobatsa boemo ba matitjhere mabapi le ho ba sedi ka dipuo tse molemo tse susumetsang ho sebediswa ha ICT. E boetse e senola ditlwaelo tsa matitjhere a kgethilweng diketso tsa ho kenyelletsa ICT ka diphaposing tsa borutelo, tse kenyelletsang tlhahlobo ya tsebo ya barutwana mehleng ya dilemo tsa ngwahaketekgolo ya 21 le hore na dithibelo tsa maemo a ho kenyelletsa ICT di ile tsa sebetswa jwang. Diphuputso tsena di totobatsa dintlha tsa ho kenyeletswa ha ka hara meralo ya Leano le dikgeo tsa Leano la Kharikhulamo le Tekolo, 2009 le Kharikhulamo ya Saense le Theknoloji bakeng sa Kereiti ya 7. Diphuputso tsena di kgothaletsa hore matitjhere a tswele pele ho ntlafatsa tsebo ya ona ya ICT le thuto ya bona; matitjhere a nke boikarabelo ba ho ntlafatsa mesebetsi ya ona e le hore a dumellane le a lefatshe ka kakaretso; tshehetso bakeng sa matitjhere a nang le boiphihlelo bo kenyelletsang ICT ho ba mohlala bakeng sa thuto ya ICT le ho ntshetsa pele Mekgatlo ya Tshebetso bakeng sa ho kenyeletswa ha ICT. Diphuputso di ile tsa etsa tlhahiso ya mokgwa wa ho kenyelletsa ICT ka katleho dikolong tsa poraemari tse ka tataisang tsamaiso ya thuto, bahlahisi ba mananeo a thuto, matitjhere le bangodi ba maano ka ho kgetheha, ka leano la ICT bakeng sa thuto Lesotho eo hona jwale e leng sethaleng sa moralo. Thuto ena e boetse e fana ka tataiso bakeng sa dithuto tsa nakong e tlang.
Ukuhlanganisa Ubuchwepheshe Bolwazi Nokuxhumana ekufundiseni nasekufundeni isayensi eLesotho
Thesis (Ph.D.(Subject Education in Science & Technology))--University of the Free State, 2023
Keywords: Inligting- en Kommunikasietegnologie (IKT); Information and Communication Technology (ICT); IKT-integrasie; ICT integration; diskoers; Discourse; Wetenskaponderrig; Science instruction; Tegnologiese Pedagogiese Inhoudskennis (TPACK) raamwerk; Technological Pedagogical Content Knowledge (TPACK) framework; die High Possibility Classroom (HPC) model; High Possibility Classroom (HPC) model; klaskamerpraktyke; Classroom practices; basiese onderwys; Basic education; Indiensonderwysers; In-service teachers; onderrig en leer; Teaching and learning; Ubuchwepheshe Bolwazikuxhumana (ICT); ukuhlanganiswa kwe-ICT; inkulumo; imfundo yesayensi; uhlaka lweTechnological Pedagogical Content Knowledge (TPACK); imodeli iHigh Possibility Classroom (HPC); izindlela zasekilasini; imfundo eyisisekelo; othisha abathwasayo; ukufunda nokufundisa; Theknoloji ya Lesedi le Dipuisano (ICT); ho kenyeletswa ha ICT; puo; thuto ya mahlale; moralo wa Technological Pedagogical Content Knowledge (TPACK); mokgwa wa High Possibility Classroom (HPC); diketso tsa ka phaposing ya borutelo; thuto ya motheo; matitjhere a sebetsang; ho ruta le ho ithuta